Analysis of the distribution of mineral royalties to municipalities affected by mining activity: Implications for the socioeconomic development of Barcarena, Pará, Brazil (Research, Society and Development, 2021)
As of Law Nº 13,540, of December 18, 2017, municipalities impacted by the mining activity started to benefit from the Financial Compensation for the Exploitation of Mineral Resources (CFEM), mineral royalties. Therefore, the aim of this article is to analyze the potential contribution of CFEM in the socioeconomic development of the municipality of Barcarena, located in the state of Pará, which is impacted by the logistics of large mining projects. The methodology used in the study consisted of bibliographic research, analysis of Brazilian legislation, in addition to the collection and analysis of CFEM data provided by the National Mining Agency (ANM). The results show that during the period from April 2019 to April 2021, the municipal government of Barcarena received R$ 3,840,920.74 in financial compensation, as it location is affected by the presence of pipelines and port operations in its territory. These amounts are insignificant compared to those received by the main ore producing municipalities in the Brazilian Amazon. It turns out that there is little transparency in relation to the policies and destinations that are being given to these resources by local governments. Furthermore, society does not participate in decision-making on the application of this important instrument for local development. Therefore, it can be concluded that it is necessary to plan and implement public policies to promote the socioeconomic development of Barcarena, in addition to promoting the verticalization of mineral production chains for greater employment and income generation, and in economic diversification of the municipality.